2018
DOI: 10.1111/een.12499
|View full text |Cite
|
Sign up to set email alerts
|

Dark butterflies camouflaged from predation in dark tropical forest understories

Abstract: 1. Morphological characteristics, especially coloration, are related to thermoregulation and camouflage, both of which are crucial for species survival and fitness. In cool environments such as the understorey of closed rainforests, darker organisms have thermal advantages and may be able to absorb heat more efficiently. However, such habitats are also suitable for darker organisms with respect to camouflage, making it difficult to elucidate whether the association of dark-coloured organisms with shady environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…By contrast, in the shady understorey of dense tropical forests, white models showing the highest luminance were the most frequently attacked by birds. This finding is in line with the results of Cheng et al (), who found that black butterfly models in tropical forests experienced lower predation rates in shady habitats than in open habitats, whereas white models showed the opposite pattern.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…By contrast, in the shady understorey of dense tropical forests, white models showing the highest luminance were the most frequently attacked by birds. This finding is in line with the results of Cheng et al (), who found that black butterfly models in tropical forests experienced lower predation rates in shady habitats than in open habitats, whereas white models showed the opposite pattern.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, in the shady understorey of dense tropical forests, white models showing the highest luminance were the most frequently attacked by birds. This finding is in line with the results of Cheng et al (2018), who found that black butterfly models in tropical forests experienced lower predation In our tropical sites, models of different colors were generally attacked at similar rates (except for the brightest, most attacked, white models), which may be explained by a decreased ability of birds to discriminate colors in the understory of tropical forest due to low light intensity (Gomez et al, 2014;Olsson, Lind, & Kelber, 2015).…”
Section: Effects Of Model Color On Predator Attackssupporting
confidence: 92%
See 2 more Smart Citations
“…Traditionally, Bogert's rule has been applied mainly to ectotherms (Clusella Trullas et al 2007) and Gloger's rule was formulated for endotherms, although the possibility that it also applies to ectotherms was left open (Rensch 1929). Past and recent work indicates that these rules could apply more broadly across animals (Amtmann 1965;Xing et al 2016;Friedman & Reme s 2017;Cheng et al 2018;Delhey 2018;Galv an et al 2018), fungi (Cordero et al 2018) and perhaps even in plants Figure 4 The association between the strength of the climatic (temperature [a, d], annual precipitation [b, e]) and environmental (tree cover [c, f]) effects on female (red) and male (blue) plumage lightness and the correlation between temperature and rainfall for different bird families (a) -(c), 65 families with 10 or more species, but results are similar using only families with 15 or more species, Table S3) or zoogeographic realm (d-f), 11 realms). Each dot depicts a family-or realm-specific effect.…”
Section: Discussionmentioning
confidence: 99%